Integrated urban water management with micro storages developed as an IoT-based solution – The smart rain barrel. (May 2021) - Oberascher, Martin; Kinzel, Carolina; Kastlunger, Ulrich; Kleidorfer, Manfred; Zingerle, Christoph; Rauch, Wolfgang; Sitzenfrei, Robert
Abstract: Low cost sensors are emerging alongside innovative data transfer technologies, allowing the integration of smart solutions for the decentralisation of water infrastructure. In this work, the smart rain barrel (SRB) concept is introduced as an IoT-based solution for advanced rainwater harvesting. The SRB consists of a rain barrel extended by a discharge valve, which is centrally controlled. This concept offers (1) individual control of each implemented SRB with its incorporation into the integrated water system management and (2) a simple large-scale implementation of additional storage units as an alternative to future expansion of existing infrastructure. The open-source software "Smartin" is developed by hypothetically retrofitting an Alpine municipality with SRBs to evaluate the effects of the latter on the urban water infrastructure. Compared to uncontrolled rain barrels, a simple coordinated control strategy already clearly improves the performance of the integrated system by reducing combined sewer overflow and addressing drinking water demand. Highlights: Smart rain barrel as an IoT-based solution for rainwater harvesting is introduced. Alpine municipality subjected to hypothetical retrofitting is used as a case study. Performance comparison of control under perfect and historical weather forecasts. Effects on both urban drainage and water supply systems are combinedly evaluated. Enabling coordinated system wide control strategies for large-scale implementations.